An Analysis of CO2-driven Cold-water Geysers in Green River, Utah and Chimayo, New Mexico - (:unkn) unknown (My University, 2014)
The eruption periodicity, CO2 bubble volume fraction, eruption velocity, flash depth and mass emission of CO2 were determined from multiple wellbore CO2-driven cold-water geysers (Crystal and Tenmile geysers, in Utah and Chimayó geyser in New Mexico). Utilizing a suite of temporal water sample datasets from multiple field trips to Crystal geyser, systematic and repeated trends in effluent water chemistry have been revealed. Crystal geyser has a four part eruption cycle composed of a minor eruption period (mEP), major eruption period (MEP), aftershock eruption period (Ae) and recharge (R). Tenmile geyser has a four part eruption cycle composed of MEP, drainage (D), mEP and R. Chimayó geyser has a two part eruption cycle composed of a MEP and R. The MEP at Crystal geyser currently lasts for over 24 hours highlighting the potential for a natural geyser to reach quasi steady state discharge. At shallow depths the bubble volume fraction ranges from 0 to 0.8, eruption velocities range from 2 to 20 m/s and flash depths are predominately shallow ranging from 5 to 40 meters below the surface. Annual emission of CO2 is estimated to be (4.77±1.92)×103, (6.17±1.73)×101, (6.54±0.57)×101 tonnes/yr for Crystal, Tenmile and Chimayó geysers, respectively. Inverse modeling of endmembers for the mEP at Crystal geyser show that the effluent is comprised of 66%, 33% and 1% the Navajo Sandstone, Entrada Sandstone and Fault Brine, respectively. The range of input for the Navajo, Entrada and Brine during the MEP is 53-57%, 42-45% and 1-2%, respectively. The geyser plumbing geometry consists of a vertical wellbore which allows for the upward migration of CO2-rich fluids due to artesian conditions. The positive feedback system of a CO2-driven eruption occurs within the well. Mitigating high velocity CO2-driven discharge from wellbores will, however, be easier than mitigating diffuse leakage from faults or into groundwater systems.
Keywords: CO2 Sequestration; Geyser; Green River